Studi Kasus Peningkatan Frekuensi Makan dengan Pijat Tui Na pada Balita Stunting: Case Study of Increasing Eating Frequency with Tui Na Massage in Stunted Toddlers - Anggi Puspitasari; Fauziah Hanum Nur Adriyani; Arlyana Hikmanti (Journal of Holistics and Health Sciences (JHHS), 2023)
Based on the World Health Organization (WHO) in its 2022 report, it shows that globally, there are 149.2 million children under the age of 5 experiencing stunting, 45.4 million are underweight, and 38.9 million are overweight. In 2010, there was a slight decrease in stunting in toddler data, namely 36.8%. and in 2013 it increased to 37.2%. The success of the government program is shown by reducing the prevalence of stunting under five in 2018 to 30.8%. However, it is still a problem because the prevalence rate is more than 20%. Data obtained from the Banjarnegara District Health Service in 2023, the number of toddlers who came to be weighed at the posyandu was 61,387 toddlers, there were 4,844 (7.9%) malnourished toddlers, 13,951 (22.7%) stunted toddlers, 35 (0.06%) ) malnutrition. Based on data obtained from the Mandiraja 1 Community Health Center, 1003 toddlers were weighed, 123 (12.2%) were malnourished, and 294 (29.3%) were stunted. One of the complementary actions taken to overcome difficulty eating in toddlers is Tui Na Massage which has the function of increasing appetite so that nutrition is met. The purpose of Tui Na Massage care is because there are still many cases of stunted toddlers with complaints that the frequency of eating is reduced so that the toddler's energy intake is not met, causing failure in growth and development. The method used for 5 stunted toddlers was using the interview method, namely asking questions and giving respondents a table. food records for 3 days to determine the frequency of eating in stunted toddlers. The research results showed that the majority of toddlers experienced an increase in eating frequency, 4 out of 5 toddlers and there was 1 toddler who did not experience an increase in eating frequency but his portion size increased. Suggestions to midwives and other health tasks can improve the quality of health services, especially for stunted toddlers, one of which is complementary action, namely tui na massage. ABSTRAK Berdasarkan World Health Organization (WHO) dalam laporan Tahun 2022 menunjukan bahwa secara global, terdapat 149,2 juta anak dibawah usia 5 tahun mengalami stunting, 45,4 juta kurus, dan 38,9 juta kelebihan berat badan. Pada tahun 2010, data balita stunting terjadi sedikit penurunan yaitu sebesar 36,8 %. dan pada tahun 2013 meningkat menjadi 37,2%.  Upaya keberhasilan program pemerintah ditunjukan melalui penurunan prevalensi balita pendek pada Tahun 2018 menjadi 30,8%. Namun masih menjadi masalah karena angka prevalensi lebih dari 20%. Data yang diperoleh dari Dinas Kesehatan Kabupaten Banjarnegara tahun 2023 jumlah balita yang datang dilakukan penimbangan di posyandu sebanyak 61.387 balita, terdapat hasil 4.844 (7,9%) gizi kurang, 13.951 (22,7%) balita pendek, 35 (0,06%) gizi buruk. Berdasarkan  data yang didapatkan dari Puskesmas Mandiraja 1 terdapat balita yang dilakukan penimbangan sebanyak 1003 balita, terdapat hasil 123 (12,2%) gizi kurang, dan 294 (29,3 %) balita pendek. Salah satu tindakan komplementer yang dilakukan untuk mengatasi sulit makan pada balita yaitu dilakukannya Pijat Tui Na yang mempunyai fungsi untuk meningkatkan nafsu makan agar nutrisinya terpenuhi. Tujuan dilakukan asuhan Pijat Tui na karena masih banyaknya kasus balita stunting dengan keluhan frekuensi makannya berkurang sehingga asupan energi pada balita tidak terpenuhi maka menyebabkan gagal dalam pertumbuhan dan perkembangan.Metode yang dilakukan kepada 5 balita stunting dengan menggunakan metode wawancara yaitu menanyakan pertanyaan dan memberikan responden tabel food records selama 3 hari untuk mengetahui frekuensi makan pada balita stunting. Hasil penelitian diperoleh sebagian besar balita mengalami peningkatan frekuensi makan sebanyak 4 dari 5 balita dan ada 1 balita yang tidak mengalami peningkatan frekuensi makan tetapi porsi makannya naik. Saran kepada bidan dan tugas kesehatan lainnya dapat meningkatkan mutu pelayanan kesehatan terutama pada balita stunting salah satunya dilakukan tindakan komplementer yaitu pijat tui na.